The relationship between agency theory, stakeholder theory and Shariah supervisory board in Islamic banking: An attempt towards discussion. Issue 1 (13th February 2017) - Al-Nasser Mohammed, Sulaiman Abdullah Saif; Muhammed, Joriah
Abstract : Purpose: In relation to the critical problem, this paper aims to present an understanding of the agency theory and the stakeholder theory from the perspective of the Islamic principles. Indeed, a thorough examination of the theoretical background explaining corporate governance from the Islamic perspective is necessary to conduct research analysing corporate governance in Islamic banks. Design/methodology/approach: The authors followed a critical review discussion; this method takes into consideration presenting important theories and comparing those theories with Islamic perspective. Findings: The authors presented important arguments on the difference between ordinary theories to explaining corporate governance and Islamic perspective. The paper browsed into whether the Shariah Supervisory Board is a fit with the agency theory by explaining the agency theory and how it differs from the Islamic banking concepts. The paper involved an analytical review on stakeholder theory and presented a critique and the rationale as to why there is ample room for the Shariah Supervisory Board to be considered a fit with the stakeholder theory, as the Shariah Supervisory Board is an independent body influencing the firm. Originality/value: The paper is of important value to those conducting research in the area of governance in Islamic banks; they may find it beneficial in terms of underlining theory building their research framework.